Theoretical aspects of computing – ICTAC 2016 : 13th International Colloquium, Taipei, Taiwan, ROC, October 24-31, 2016, Proceedings /: 13th International Colloquium, Taipei, Taiwan, ROC, October 24-31, 2016, Proceedings. (2016) - Unknown
No abstract available